Perceived Risks and Benefits of Cigarette Smoking among Nepalese Adolescents: A Population-Based Cross-Sectional Study - Aryal, UR; Petzold, M; Krettek, A (2016)
Background: Perceived risks and benefits of smoking play an important role in susceptibility to smoking among adolescents. Our study examined perceived smoking-related risks and benefits among adolescents who were susceptible (i.e., adolescents who did not express a strong commitment not to smoke) and not susceptible to smoking. Methods: We conducted a population-based, cross-sectional study in Jhaukhel and Duwakot, two villages in Nepal's Bhaktapur District, during October–November 2011. Trained enumerators used a semi-structured questionnaire to interview 500 randomly selected 14- to 16-year-old adolescents. The enumerators asked the adolescents to estimate their likelihood (0%–100%) of experiencing various smoking-related risks and benefits of smoking in a hypothetical scenario. Results: Principal component analysis extracted four perceived risk and benefit components, excluding addiction risk: (i) physical risk I (lung cancer, heart disease, wrinkles, bad colds); (ii) physical risk II (bad cough, bad breath, and trouble breathing); (iii) social risks (getting into trouble, smelling like an ashtray); and (iv) benefits (looking cool, feeling relaxed, becoming popular, and feeling grown-up). The adjusted odds ratio of susceptibility increased 1.20-fold with each increased quartile in perceptions of physical risk I. Susceptibility to smoking was 0.27- and 0.90- fold less among adolescents who provided the highest estimates of physical risk II and social risks, respectively. Similarly, susceptibility was 2.16-fold greater among adolescents who provided the highest estimates of addictive risk. Physical risk I, addiction risk, and benefits of cigarette smoking related positively, and physical risk II and social risk related negatively, with susceptibility to smoking.